A comparison of sodium contents on nutrition information labels of foods with and without nutrition claims marketed in Brazil. Issue 7 (4th July 2016) - Nishida, Waleska; Fernandes, Ana Carolina; Veiros, Marcela Boro; González Chica, David Alejandro; Proença, Rossana Pacheco da Costa
Abstract : Purpose: To compare the sodium content displayed on the labels of conventional processed food products (C) and of those with nutrition claims suggesting the absence or reduced levels of nutrients (AR). Design/methodology/approach: Cross-sectional study analyzing the ingredients list, nutrition facts and nutrition claims on food labels. Subjects: All processed food products with added salt or additives containing sodium that were for sale in a large supermarket in Brazil from October to December 2011. Findings: All 3, 449 products were analysed and categorized into 66 groups according to Brazilian legislation. The median of sodium content in the AR was 42.7% higher than in the C (P=0.007). In 33.3% of the groups there was difference in sodium content between AR and C (p<0.05) and in 68.2% of these the sodium content was higher in AR. The variation range of sodium in products from the same group reached 2, 905.0mg in C and 1, 712.0mg in AR. Even when the median of sodium was lower in the AR, the minimum sodium values were lower in the C. Originality/value: Comparisons of sodium content of conventional and AR processed food are scarce in the literature, especially covering all food for sale in a large supermarket. To the best of our knowledge, this is the first census making this comparisons in Latin America.